2017
DOI: 10.1088/1674-1056/26/9/093106
|View full text |Cite
|
Sign up to set email alerts
|

Lattice stability and the effect of Co and Re on the ideal strength of Ni: First-principles study of uniaxial tensile deformation

Abstract: Using first-principles density functional calculations, lattice stability of γ-Ni under [001], [110], and [111] uniaxial tensions and the effect of alloying elements Co and Re on the uniaxial tensile behavior of γ-Ni were studied in this paper. With elastic constants and phonon spectra calculations, we examined the mechanical stability and phonon stability of Ni during the uniaxial tensions along the three characteristic directions. The results show that the mechanical stability and phonon stability of a latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…As verified in our previous studies, [33,44] the mechanical stability of the crystal lattice of γ -Ni 3 Al will be maintained until the first maximum point of the stress-strain curve during [110] tensile and (111) [11 2] shear deformation. If there is no other instability mode (e.g., soft phonon instability or magnetic spin arrangement [45][46][47][48] ), the corresponding stress of this peak point, denoted by σ FM and τ FM respectively, for the tensile and shear process, is exactly the ideal strength of γ -Ni 3 Al under the specified loading. Herein, the corresponding strain of the peak point of the stress-strain curve is defined as the first maximum strain (expressed by ε FM and γ FM for tensile and shear deformation, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…As verified in our previous studies, [33,44] the mechanical stability of the crystal lattice of γ -Ni 3 Al will be maintained until the first maximum point of the stress-strain curve during [110] tensile and (111) [11 2] shear deformation. If there is no other instability mode (e.g., soft phonon instability or magnetic spin arrangement [45][46][47][48] ), the corresponding stress of this peak point, denoted by σ FM and τ FM respectively, for the tensile and shear process, is exactly the ideal strength of γ -Ni 3 Al under the specified loading. Herein, the corresponding strain of the peak point of the stress-strain curve is defined as the first maximum strain (expressed by ε FM and γ FM for tensile and shear deformation, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…The stabilities of these compounds are studied from the mechanical properties. [32] Based on Born-Huang's lattice dynamics theory, the strain energy of the mechanical stability of a structure must be positive in one of the conditions for any uniform elastic deformation as indicated below. [30,33,34] For cubic system (for Cr 3 Si, CrSi):…”
Section: Mechanical Stability and Elastic Propertiesmentioning
confidence: 99%
“…Experiment has reported that the order of improvement in creep-strengthening is Ta < W < Re. [13] The strengthening effects of Ta, W, and Re on Ni-based superalloys were mainly focused on γ matrix, γ -matrix, and the coherent region of the γ/γ interface in previous studies, [19][20][21][22][23][24][25][26][27] so we will study the strengthening effects of the doped atoms in the dislocation core of the γ/γ interface and explain the reason why the doped atoms have different strengthening effects in the [110] (001) dislocation core at electronic level.…”
Section: Introductionmentioning
confidence: 99%